Evaluation of Pediatric Patients’ General Health Status Prior to Dental Treatment Under General Anesthesia: A Retrospective Study - Enes Bardakçı; Şemsettin Yıldız; Betül Yazmacı; Mehmet Emin Doğan; Kübra Mumcu; Mehmet Sinan Doğan (Children, 2025)
Background/Aim: Dental treatment is typically performed under general anesthesia for children who have difficulty cooperating, as well as for those with mental or physical disabilities requiring special care. This study aims to categorize and evaluate the systemic disease or syndrome status, age, and gender of children who require dental treatment under general anesthesia. Materials and Methods: In this study, the ages, sexes, disabilities (if any), and systemic diseases of patients requiring dental treatment under general anesthesia (GA) between the ages of 1 and 15 were analyzed. The patients were categorized based on having difficulties cooperating or having mental or physical disabilities that require special care. Results: In this study, data from 1666 patients were examined. A total of 955 patients (57.32%) were male, while 711 (42.67%) were female. Overall, 232 (13.9%) patients with disabilities or systemic diseases visited the clinic, including 49 who had epilepsy (2.9%), the highest number among the systemic disease group. This finding was statistically significant in the 4–6 age group (p < 0.00). Conclusions: Among patients with special needs, epilepsy emerged as a disorder that requires the most dental treatment. We believe that providing dental treatment for children with neurological diseases, such as epilepsy, in a fully equipped operating room will be beneficial in managing complications that may arise during treatment.